Novel modulo multipliers for moduli 2^n-1, 2^n and 2^n+1. - Ramya Muralidharan (2012)
Long word-length integer multiplication is widely acknowledged as the bottleneck operation in public key cryptographic and signal processing algorithms. Residue Number System (RNS) has emerged as a promising alternative number representation for the design of faster and low power multipliers owing to its merit to distribute a long integer multiplication into several shorter and parallel modulo multiplications. To maximize the advantages offered by the RNS multiplier, judicious choice of moduli that constitute the RNS base and design of efficient modulo multipliers are imperative. In this thesis, special modulo 2^n-1, modulo 2^n and modulo 2^n+1 multipliers are studied. By manipulating the number theoretic properties of special moduli, 2^n-1, 2^n and 2^n+1, new low-power and low-area modulo multipliers are proposed.